Ta có:
\(\sqrt{50}+\sqrt{26}+1>\sqrt{49}+\sqrt{25}+1\)
\(=7+5+1=13\)
Mà \(\sqrt{168}< \sqrt{169}=13\)
Vì \(\sqrt{50}+\sqrt{26}+1>13>\sqrt{168}\)
Nên \(\sqrt{50}+\sqrt{26}+1>\sqrt{168}\)
Ta có :
\(\sqrt{50}+\sqrt{26}+1>\sqrt{49}+\sqrt{25}+1=7+5+1=13=\sqrt{169}>\sqrt{168}\)
Vậy \(\sqrt{50}+\sqrt{26}+1>\sqrt{168}\)
Chúc bạn học tốt ~
Ta có :\(\sqrt{50}+\sqrt{26}+1>\sqrt{49}+\sqrt{25}+1\)
\(=>\sqrt{50}+\sqrt{26}+1\)\(>7+5+1=13\)
Mà \(\sqrt{168}=13\)
\(=>\sqrt{50}+\sqrt{26}+1>\sqrt{168}\)
Trả lời:
Vì\(0< 168< 169\)
\(\Rightarrow\sqrt{168}< \sqrt{169}\)
\(\Leftrightarrow\sqrt{168}< 13\)(1)
Mà\(13=7+5+1\)
\(\Rightarrow13=\sqrt{49}+\sqrt{25}+1\)
Vì\(50>49>0\)
\(\Rightarrow\sqrt{50}>\sqrt{49}\)
\(26>25>0\)
\(\Rightarrow\sqrt{26}>\sqrt{25}\)
Do đó: \(\sqrt{50}+\sqrt{26}>\sqrt{49}+\sqrt{25}\)
\(\Rightarrow\sqrt{50}+\sqrt{26}+1>\sqrt{49}+\sqrt{25}+1\)
Hay\(\sqrt{50}+\sqrt{26}+1>13\)(2)
Từ (1) và (2) \(\Rightarrow\sqrt{50}+\sqrt{26}+1>\sqrt{168}\)
Vậy\(\sqrt{50}+\sqrt{26}+1>\sqrt{168}\)
Hok tốt!
Vuong Dong Yet
Bạn kia là bạn nào mới quan trọng